Increasing Students' Learning Motivation Through Dicovery Learning-Based Educational Game Media Technology - Dia , Erina Rahma; Putri, Agustiany Dumeva; Zahra, Atika (Journal of Curriculum and Pedagogic Studies (JCPS), 2024)
The number of students who experience difficulties in understanding mathematical concepts is due to monotonous teaching methods that cause indifference and lack of motivation for students to learn in learning. This research aims to enable teachers to utilize technology as an interactive learning medium to increase students' learning motivation in understanding mathematical concepts by presenting the concept of educational games. The educational game media used is based on discovery learning, which means that with discovey learning, students will be encouraged to discover mathematical concepts and explore new knowledge through exploration. The research subjects used were grade VIII students at SMP Negeri 40 Palembang. The research method used is Research and Development research with development studies, whose stages are adjusted to the tessmer development model. Based on the results of the research in the field test stage trial, with the data collection techniques being learning motivation questionnaires, student response questionnaires and interviews, it was stated that discovery learning-based educational game media had a positive influence on increasing students' learning motivation. This is evidenced by the enthusiasm of students in participating in learning, they compete to achieve the highest score and be the fastest to solve the challenge in the educational game and also based on the results of data analysis which shows that the average score of the student learning motivation questionnaire increased to 82.76% with a high category after using the media.